Efforts to Prevent Oil Pollution During Loading and Unloading on the MT. Sanana Ship - Rizky Fathan Al Firdaus (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2026)
Background: Maritime transportation plays a vital role in energy distribution, while tanker loading and unloading operations pose a risk of oil leaks that can damage coastal ecosystems and livelihoods. Objective: This study aims to identify the causes of spills during cargo transfers at MT. Sanana, assess the impact if the leak is not immediately addressed, and formulate practical preventive measures. Method: A qualitative case study was conducted during a 12-month sea practice (August 22, 2024–August 26, 2025). The population included operational personnel and ship documents, with purposive sampling for key informants (master, chief officer, second officer, third officer). Data were collected through participant observation, semi-structured interviews, and documentation studies, analyzed using inductive thematic coding and triangulation. Results: It was found that the implementation of SOPs, the availability of oil spill kits, and routine maintenance were effective in mitigating small leaks; the main obstacles were worn gaskets and valves, procedural omissions, and suboptimal communication. Conclusion: Effective prevention requires synergy between technical maintenance, rigorous pre-operational checks, and ship-terminal coordination; Recommendations include replacing worn fittings, enforcing checklists, and regular simulation training. Limitations: single case study and participatory role of the researcher.